An investigation into the imager pointing accuracy and stability for a CubeSat Using a CubeADCS in sun-synchronous low earth orbits - Van Der Stokker, Luke (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.